Pencarian Rute Terpendek di dalam Mall menggunakan Lifelong Planning A* pada Android - Igor Maha Putra; Agustinus Noertjahyana; Justinus Andjarwirawan (Jurnal Infra, 2021)
Since past time until now, people still loves to travel and sometimes when they travel they went to a shopping center store or what we known as a mall. Inside the mall there’re a lot of facilities that wes can use/enjoy like food and beverages stands, utilities shops, clothing lines, and many more. Apart from us of course there’re another subjects that visits the mall including tourists and online taxi drivers. Of course, even them we can’t guarantee that they understand the location of the shops or facilities that they want to visit.The application will help all people who came to a particular mall. To do this, we need a server that can store the maps data and shops inside each mall. After the data collection process, the application will receive an input from the user about a shop / a facility that they want to visit, then after received an input from the user, a data calculation process will be carried out which will be shown the route that has been calculated by the application and then the results will be displayed on the application that has been made. Based on the results of the tests that have been done, the program is quite successful in storing, calculation and displaying which route the user must take.